(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2020)
The objective of the work is to analyze the masculinity models that are represented in the advertising of the Quilmes and Imperial breweries between 2017 and 2019.We seek to analyze whether media discourses continue to be associated with hegemonic masculinity knowing that there are new male and female identities.Also, we will try to detect the gender roles and stereotypes that are reinforced from advertising considering that the media are socializing agents. It is expected to detect if androcentric, heteronormative and classist looks are reproduced.Finally, continuities and changes in the stories around the concept of symbolic violence will be analyzed. And the association of alcohol consumption with the idea of happiness, conquest, brotherhood, the relation with sport, and its consequences will be problematized.